2021
DOI: 10.1038/s41418-021-00781-4
|View full text |Cite|
|
Sign up to set email alerts
|

PLK1/vimentin signaling facilitates immune escape by recruiting Smad2/3 to PD-L1 promoter in metastatic lung adenocarcinoma

Abstract: The prerequisite function of vimentin for the epithelial–mesenchymal transition (EMT) is not clearly elucidated yet. Here, we show that vimentin phosphorylated by PLK1, triggers TGF-β-signaling, which consequently leads to metastasis and PD-L1 expression for immune suppression in lung adenocarcinoma. The clinical correlation between expression of both vimentin and PLK1, and overall survival rates of patients was significant in lung adenocarcinoma but not in squamous cell carcinoma. The phosphorylation of vimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 61 publications
3
48
0
Order By: Relevance
“…44 In a recent study, it has been reported that PLK1mediated phosphorylation of vimentin can also activate TGFβ signaling pathway, leading to the metastasis and immune escape through the expression of PD-L1 which can serve as a shuttling protein in lung adenocarcinoma. 45 Therefore, the increase in vimentin- interest that miRNA-155 promotes cervical cancer cell proliferation through suppression of its target gene LKB1. 48 In addition, there are reports showing that expression of LKB1, an upstream kinase of AMPK, impeded TGFβ-induced Smad phosphorylation and their transcriptional activity in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…44 In a recent study, it has been reported that PLK1mediated phosphorylation of vimentin can also activate TGFβ signaling pathway, leading to the metastasis and immune escape through the expression of PD-L1 which can serve as a shuttling protein in lung adenocarcinoma. 45 Therefore, the increase in vimentin- interest that miRNA-155 promotes cervical cancer cell proliferation through suppression of its target gene LKB1. 48 In addition, there are reports showing that expression of LKB1, an upstream kinase of AMPK, impeded TGFβ-induced Smad phosphorylation and their transcriptional activity in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with previous studies demonstrating that high expression of VIM or ITGB2 is related to cancer progression and metastasis [ 89 , 90 , 91 , 92 , 93 ]. In addition, hypoxia [ 94 , 95 , 96 ] and TGFβ [ 97 , 98 , 99 , 100 ] have been shown to induce VIM and ITGB2 expression. Although the effect of hypoxia on ITGB2 activity has not yet been described, hypoxia is known to be involved in the routing, recycling, and activation of various integrin β subunits [ 101 , 102 , 103 ], suggesting that it may also have an effect on ITGB2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…ANLN promotes LUAD progression via activating RHOA and involving the PI3K/AKT signaling ( Suzuki et al, 2005 ). PLK1/vimentin pathway promotes immune escape through recruitment of Smad2/3 to PD-L1 promoter in LUAD metastasis ( Jang et al, 2021 ). PLK1 induces migration of LUAD epithelial cells through STAT3 ( Yan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%